Sustainable Finance Practices And Their Impact On Corporate Financial Performance - Anggraini, Diah; Moridu, Irwan; Siddiqa, Heidi; Dewantara, Billy; Nurcahaya, Claudya (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This study aims to analyze the impact of sustainable finance practices on corporate financial performance using a literature review approach. Sustainable finance, reflected in the implementation of Environmental, Social, and Governance (ESG) principles, has become a critical issue in modern business as awareness of sustainability and corporate social responsibility continues to grow. The research method employed is a systematic literature review of relevant academic sources, including peer-reviewed journals, scholarly books, and institutional reports published between 2010 and 2025. The findings indicate that sustainable finance practices generally have a positive impact on corporate financial performance, particularly in the long term. Improvements in operational efficiency, corporate reputation, risk management, and access to financial resources are key drivers of this positive relationship. However, the results also reveal that the relationship is not always consistent, as it is influenced by contextual factors such as industry type, firm size, and regulatory environment. In addition, in the short term, sustainable finance practices may have a negative impact due to the high costs associated with their implementation. This study concludes that sustainable finance is a strategic approach that can enhance long-term corporate value, although it requires an integrated and long-term orientation. The findings are expected to provide insights for corporations, investors, and policymakers in developing sustainable business strategies.